2016
DOI: 10.1080/1536383x.2016.1155561
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative topological accumulation of vacancies in honeycomb lattices

Abstract: Present topological study focuses on the formation mechanism of clusters of vacancies in graphenic layers. An original effect that explains both accumulation and self-healing of vacancies represents the original outcome of our investigation whose results, based on the long-range topological properties of the honeycomb lattices, are applicable to defective graphene sheets and general honeycomb lattices when other elements other than carbon are present. Some speculations about the role of long-range bondonic sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 24 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…It was found that 10% of divacancy defects reduce the thermal conductivity of graphene by 80%, and the decrease of the zigzag graphene nanoribbon is greater than that of the armchair type in the case of high defect concentration [41]. However, experimental results show that both 585, t5t7 (three pentagons and three heptagons) and f5f7 (four pentagons, four heptagons and one hexagon) divacancies are stable and common in graphene [7,42,43], and they can propagate in the structure [44,45,46] or transform each other [42,43,47]. Therefore, it is necessary to systematically study the effect of divacancies with different structures on the thermal transport properties of graphene.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that 10% of divacancy defects reduce the thermal conductivity of graphene by 80%, and the decrease of the zigzag graphene nanoribbon is greater than that of the armchair type in the case of high defect concentration [41]. However, experimental results show that both 585, t5t7 (three pentagons and three heptagons) and f5f7 (four pentagons, four heptagons and one hexagon) divacancies are stable and common in graphene [7,42,43], and they can propagate in the structure [44,45,46] or transform each other [42,43,47]. Therefore, it is necessary to systematically study the effect of divacancies with different structures on the thermal transport properties of graphene.…”
Section: Introductionmentioning
confidence: 99%
“…The t is the level that depicts graphene layers in carbon graphite, m is the number of rows and n is the number of columns in each layer, with m taken as n copies of hexagons in a row and n taken as m copies of hexagons in columns. [ 25 , 26 , 27 ] Ori et al, and [ 28 ], Jagadeesh discussed the topological behaviour of some graphene. In Figure 1 , the levels of carbon graphite is , and , where is taken as copies of hexagons in a row in each level , and is taken as copies of hexagons in columns in each level.…”
Section: Structure Of Carbon Graphitementioning
confidence: 99%
“…We should mention that in this work first principle calculations and density functional theory (DFT) have been employed to obtain our numerical results. They are the specific implements to investigate the different properties of graphene with defects [18][19][20][21][22], doped graphene nanoribbons [23][24][25][26], or other nanowires [27].…”
Section: Introductionmentioning
confidence: 99%